Determinants of women’s perceived satisfaction on Antenatal care in urban Ghana: A cross-sectional study - Asafo, Akowuah Jones; Adoma, Danquah Benedicta (Clinical Journal of Obstetrics and Gynecology, 2019)
Despite evidence on major interventions on the uptake and scale up of interventions meant to promote maternal health care services, little is known about adequate use of such program in urban Ghana among reproductive aged women. This study examined the determinants of women’s Satisfaction on antenatal care use in selected health facilities in the Kwabre East Municipality of Ghana. Using facility-based cross-sectional survey design, a three-stage sampling technique was conducted to sample 220 women attending postnatal care at selected public health facilities. Open-ended questionnaires were used to obtain data from respondents. Descriptive statistics and inferential statistics including binary logit regression model were used to analyze the data with the help of SPSS and STATA software. Logit analytical framework was computed to determine equations of variance. The association between antenatal care use and women’s satisfaction was determined and assessed using Pearson’s χ2 (2) test indicating 1% was run. Most women (92.7%) had at least four ANC visits during their entire pregnancy. The results indicate standard deviation of 7 with 81% regular ANC visits and 19% irregular. Most women (55%) received care by one caregiver, followed by women (35%) who received care by two caregivers and women (10%) who were cared for by three caregivers. The regression results showed varying utilization levels of 10%, 5% & 1% ANC satisfaction. System induced factors aimed at promoting maternal care use satisfaction are suggested.